Rodinný dům - Kavečková, Hana (Vysoké učení technické v Brně. Fakulta stavební, 2018)
Předmětem bakalářské práce je vypracování dokumentace pro provedení stavby rodinného domu v obci Medlovice (okr. Vyškov). Stavba je navržena jako částečně podsklepený objekt se dvěma nadzemními podlažími. V suterénu se nachází technické zázemí a prostory pro odpočinek. První nadzemní podlaží je převážně pro společenské účely s přístupem na terasu a dvůr. Dále je zde garáž pro dva automobily a dílna. Druhé nadzemní podlaží je převážně odpočinkové, nachází se zde ovšem i pracovna a studovna. Zastřešení je řešeno konstrukcí ze sbíjeného vazníku se spádem 23° sedlového tvaru. Zastřešení přilehlé garáže je zároveň konstrukcí balkonu. Stavba je navržena ze systému pórobetonových tvárnic YTONG, kromě suterénního obvodového zdiva, které je tvořeno z tvárnic ztraceného bednění BEST. Po celém obvodu domu je kamenný obklad.

The subject of the bachelor thesis is the elaboration of documentation for the construction of a family house in the village of Medlovice (district of Vyškov). The building is designed as a partly basement building with two above-ground floors. In the basement there are technical facilities and spaces for relaxation. The first floor is mostly for social purposes with access to the terrace and courtyard. There is also a garage for two cars and a workshop. The second floor is mostly relaxing, but there is also a study and working room. Roof is solved by the construction of a nailing truss with a slope of 23 ° of a saddle shape. Roofing of the adjoining garage is also a construction of the balcony. The building is designed from the Ytong porous concrete system, except the masonry of the basement, which is made from blocks of Best lost formwork. Through the entire perimeter of the house there is stone tiling.
Family residence
Keywords: Rodinný dům; částečné podsklepení; sbíjený vazník; ztracené bednění; pórobetonové tvárnice; tepelně-izolační nosník.; Family house; partial basement; nailing truss; lost formwork; porous concrete block; thermal insulation beam.